PENGARUH METODE DEBAT AKTIF TERHADAP MOTIVASI BELAJAR IPS PESERTA DIDIK KELAS VI UPTD SDN 188 KABUPATEN BARRU - Rafidah Muthtmainnah; Muhammad Nawir; Nurdin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main problem in this study is student learning motivation in social studiesincluding boredom eleck of understanding of social studients concepts. This studyaims to improve the learning motivation of sixth-grade students at the UPTD SDN188, Barru Regency. This research and uses a describetive survey method. Fivemeetings werw conducted. The research procedure included planning,implamentation, action, observation, and reflection. The subjects in the studywere 18 sixth-grade students at the UPTD SDN 188, Barru Regency. The resultindicate that student learning motivation. Based on the results of the product-moment correlation analysis using SPSS, the debate method variable significantlycontributed to motivation. The learning achievement was 45.51%, and thecalculated the value was greeter than the table, proving that the data wassignificant. Based on these research results, it can be concluded that theapplication of the active debate methode can increase the learning motivation ofsixth-grade students at the UPTD SDN 188, Barru Regency.